PERBANDINGAN PROBLEM BASED LEARNING DENGAN PROJECT BASED LEARNING BERBANTUAN MEDIA AUDIO VISUAL DITINJAU DARI HASIL BELAJAR - R, Mardiana; Nursalam; Fithriani Saleh, Siti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This study aims to compare the social studies learning outcomes of fifth-grade students in Cluster 1, Bontoala Subdistrict, Makassar City, who were taught using the Problem-Based Learning (PBL) model with audiovisual media assistance, with those taught using the Project-Based Learning (PjBL) model with audiovisual media assistance. This research is a quantitative study with a quasi-experimental design. The sample consists of two classes: an experimental class of 30 students taught using the PBL model and a control class of 29 students taught using the PjBL model. The data analysis method used in this study is an independent sample t-test to examine the mean difference between the two groups. The results show a significant difference in students' learning outcomes between the two groups, with a significance value (Sig. 2-tailed) of 0.003 (p < 0.05). These findings indicate that the PBL model with audiovisual media assistance is more effective in enhancing student motivation and learning outcomes in social studies compared to the PjBL model with audiovisual media assistance.